Corrosion Behavior of Plasma Sprayed Cr2O3 - Al2O3 - ZrO2 Multilayer Coatings on Mild Steel. (2018) - Sreenivas Rao, K.V.; Tejaswini, G.C.; Girisha, K.G.
Abstract: In the present work, corrosion behavior of plasma sprayed Cr2 O3 - Al2 O3 - ZrO2 multilayer coatings on ASTM A36 mild steel substrate was experimented using salt spray test as per ASTM-B117. A bond coat of Ni/Cr was deposited for obtaining good adhesion between the base material and the ceramic powder materials. The coated and uncoated substrates were salt sprayed with 5% concentration NaCl and were maintained in that environment for different time periods. The surface and cross-sectional morphologies of corroded samples have been examined using SEM micrographs. Vickers micro hardness and porosity of coated and uncoated samples were measured. The presence of elements of chromium, aluminium, zirconium and oxide were confirmed in the EDX analysis. Experimental results indicate that multilayer coated substrates exhibit better corrosion resistance, increased hardness and reduced porosity as compared to uncoated substrate.